2016
DOI: 10.1590/0103-9016-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity reduction in improved durum wheat cultivars of Morocco as revealed by microsatellite markers

Abstract: It has been argued that genetic diversity in crop varieties has been on the decline in recent times due to plant breeding. This can have serious consequences for both the genetic vulnerability of crops and their plasticity when responding to changes in production environments. It is, therefore, vital for plant breeding programs to maintain sufficient diversity in the cultivars deployed for multi-period cultivation. In this study, to understand the temporal genetic diversity in durum wheat, 21 improved durum wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…This indicated the importance of such diverse bread wheat germplasm in order to improve further wheat diversity and productivity in a scenario of climate change, which has posed serious problems in recent years. Henkrar et al (2016) have also reported similar findings for enhancing genetic diversity and improving wheat productivity.…”
Section: Discussionsupporting
confidence: 59%
“…This indicated the importance of such diverse bread wheat germplasm in order to improve further wheat diversity and productivity in a scenario of climate change, which has posed serious problems in recent years. Henkrar et al (2016) have also reported similar findings for enhancing genetic diversity and improving wheat productivity.…”
Section: Discussionsupporting
confidence: 59%
“…Further, the genetic study by Kabbaj et al (2017) included 'Nassira' in sub-population 9, together with the 'Faraj'-derived lines, while it placed 'Marouane' in sub-population 7. Similarly, Henkrar et al (2016) confirmed strong genetic similarities between 'Nassira' and 'Faraj'. 'Marouane' is the only one with no support in the pedigree for the T. araraticum source of resistance, nor similarity by genetic studies (Henkrar et al 2016;Kabbaj et al 2017).…”
Section: Germplasm Lines Resistant To Hessian Flymentioning
confidence: 60%
“…Similarly, Henkrar et al (2016) confirmed strong genetic similarities between 'Nassira' and 'Faraj'. 'Marouane' is the only one with no support in the pedigree for the T. araraticum source of resistance, nor similarity by genetic studies (Henkrar et al 2016;Kabbaj et al 2017). Yet, Jlibene and Nsarellah (2011) indicated that all Moroccan cultivars released in 2003, including 'Marouane', were derived from the same T. araraticum source, with the exception of 'Amria', which was derived from cross with a bread wheat containing H5.…”
Section: Germplasm Lines Resistant To Hessian Flymentioning
confidence: 60%
“…Total of 20 bread wheat and 21 durum wheat varieties (Table 1; Henkrar et al 2015a, b) and 5 additional durum wheat varieties, Isly (released in 1988), Massa (released in 1988), Anouar (released in 1993), Sboula (released in 2000), and Chaoui (released in 2003) were used to characterize the glutenin alleles at Glu - A1 , Glu - B1 , Glu - D1 , Glu - A3 , Glu - B3, and Glu - D3 loci. Five exotic cultivars with known glutenin subunit composition (Tables 1, 2) were used as controls to confirm the exact fragment amplified.…”
Section: Methodsmentioning
confidence: 99%